Lithium-ion adsorption on surface modified porous carbon - Vijayan, Bincy Lathakumary; Amina, Yasin; Izan Izwan, Misnon; Karuppiah, Chelladurai; Yang, Chun-Chen; Rajan, Jose (Elsevier Ltd, 2023)
Lithium-ion storage in porous carbon electrodes offers challenges due to poor electrode kinetics and limited storability. In this article, we demonstrate improved lithium-ion storage kinetics and rate capability in carbon electrode with appropriate surface or void modifications. The surface of porous carbon is modified by developing a thin film of either a metal oxide (Mn2O3) or a metal (cobalt) or the large voids in them are filled using hierarchical MnCo2O4 or TiO2 nanoflowers. Lithium-ion capacitors are fabricated in the Carbon//LiPF6//Li configuration and evaluated their lithium storage performance using cyclic voltammetry, galvanostatic charge discharge cycling, and electrochemical impedance spectroscopy. While the surface or void modification nominally increased the specific capacitance, the potential window and rate capability of the resulting devices remarkably increased. Among all the tested devices, the MnCo2O4 flowers filled electrode showed the largest capacitance and capacity retention, which are ascribed to its lower lithium transfer resistance.